Estimating the effect of exchange rate changes on total exports - Thierry Mayer; Walter Steingress (Bank of Canada, 2019)
This paper shows that real effective exchange rate (REER) regressions, the standard approach for estimating the response of aggregate exports to exchange rate changes, imply biased estimates of the underlying elasticities. We provide a new aggregate regression specification that is consistent with bilateral trade flows micro-founded by the gravity equation. This theory-consistent aggregation leads to unbiased estimates when prices are set in an international currency as postulated by the dominant currency paradigm. We use Monte-Carlo simulations to compare elasticity estimates based on this new "ideal-REER" regression against typical regression specifications found in the REER literature. The results show that the biases are small (around 1 percent) for the exchange rate and large (around 10 percent) for the demand elasticity. We find empirical support for this prediction from annual trade flow data. The difference between elasticities estimated on the bilateral and aggregate levels reduces significantly when applying an ideal-REER regression rather than a standard REER approach.
Keywords: F11; F12; F31; F32; 330; Econometric and statistical methods; Exchange rates; International topics